Drivers of change and stability in the gut microbiota of an omnivorous avian migrant exposed to artificial food supplementation. Issue 19 (18th August 2021) - Pekarsky, Sasha; Corl, Ammon; Turjeman, Sondra; Kamath, Pauline L.; Getz, Wayne M.; Bowie, Rauri C. K.; Markin, Yuri; Nathan, Ran
Abstract: Human activities shape resources available to wild animals, impacting diet and probably altering their microbiota and overall health. We examined drivers shaping microbiota profiles of common cranes ( Grus grus ) in agricultural habitats by comparing gut microbiota and crane movement patterns (GPS‐tracking) over three periods of their migratory cycle, and by analysing the effect of artificially supplemented food provided as part of a crane‐agriculture management programme. We sampled faecal droppings in Russia (nonsupplemented, premigration) and in Israel in late autumn (nonsupplemented, postmigration) and winter (supplemented and nonsupplemented, wintering). As supplemented food is typically homogenous, we predicted lower microbiota diversity and different composition in birds relying on supplementary feeding. We did not observe changes in microbial diversity with food supplementation, as diversity differed only in samples from nonsupplemented wintering sites. However, both food supplementation and season affected bacterial community composition and led to increased abundance of specific genera (mostly Firmicutes). Cranes from the nonsupplemented groups spent most of their time in agricultural fields, probably feeding on residual grain when available, while food‐supplemented cranes spent most of their time at the feeding station. Thus, nonsupplemented and food‐supplemented diets probably diverge only in winter, when crop rotation and depletion of anthropogenic resources may lead to a more variable diet in nonsupplemented sites. Our results support the role of diet in structuring bacterial communities and show that they undergo both seasonal and human‐induced shifts. Movement analyses provide important clues regarding host diet and behaviour towards understanding how human‐induced changes shape the gut microbiota in wild animals.